2000
DOI: 10.1086/317319
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Long-Period Planet Orbiting ε Eridani

Abstract: High-precision radial velocity (RV) measurements spanning the years 1980.8-2000.0 are presented for the nearby (3.22 pc) K2 V star e Eri. These data, which represent a combination of six independent data sets taken with four different telescopes, show convincing variations with a period of ≈7 yr. A least-squares orbital solution using robust estimation yields orbital parameters of period yr, velocity amplitude m s Ϫ1 , ec-P p 6.9K p 19 centricity , projected companion mass , and semimajor axis AU. Ca ii e p 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
200
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(207 citation statements)
references
References 27 publications
5
200
1
1
Order By: Relevance
“…With a distance of only 3.7 pc, HD 10700 is the third closest star reported to be a host to a putative planetary system after Eridani (Hatzes et al 2000) with a distance of 3.2 pc and α Centauri B (Dumusque et al 2012) with a distance of 1.3 pc, though both of these remain to be confirmed and Zechmeister et al (2013) have casted considerable doubt on the existence of a planet around Eridani. This makes HD 10700 an ideal target for future direct-imaging missions.…”
Section: Discussionmentioning
confidence: 99%
“…With a distance of only 3.7 pc, HD 10700 is the third closest star reported to be a host to a putative planetary system after Eridani (Hatzes et al 2000) with a distance of 3.2 pc and α Centauri B (Dumusque et al 2012) with a distance of 1.3 pc, though both of these remain to be confirmed and Zechmeister et al (2013) have casted considerable doubt on the existence of a planet around Eridani. This makes HD 10700 an ideal target for future direct-imaging missions.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to be a relatively young system (<1 Gyr; Song et al 2000;Soderblom & Dappen 1989), with a mass slightly less than our own Sun. From radial velocity measurements, Hatzes et al (2000) have reported evidence for a planet in this system with a semimajor axis of 3.4 AU and m sin i ¼ 0:86M J .…”
Section: Introductionmentioning
confidence: 87%
“…We have used the robust radial velocity fit from Hatzes et al (2000) as an input for our astrometric fit to the Hipparcos intermediate astrometric data. Formally the fit from Benedict et al (2006) would have been the most precise one, but we preferred input parameters that came from a spectroscopic fit only instead of one which already was based on combined spectroscopy and HST astrometry.…”
Section: Eri (Hip 16537)mentioning
confidence: 99%